Composition, cured film, device including same, and method for producing cured film
By using polycyclic aromatic hydrocarbon polymers, scattering agents and thiol monomer-containing compositions, low-temperature curing forms a high-refractive index film, solving the performance damage caused by high-temperature curing, and improving the thickness, adhesion and transparency of the high-refractive index film, and is suitable for organic electroluminescent equipment.
Patent Information
- Application Number
- JP2024543512
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-01
- Filing Date
- 2023-01-30
- Publication Date
- 2025-02-12
AI Technical Summary
The prior art requires high temperature curing when forming high-refractive index organic films, resulting in damage to the performance of the organic functional layer and difficulty in controlling the thickness, adhesion and haze of the film.
A composition containing polycyclic aromatic hydrocarbon polymer, a scattering agent and a thiol-containing monomer is used to form a high refractive index film by low temperature curing, solubility is improved by using acidic groups of the polycyclic aromatic hydrocarbon polymer, a scattering agent enhances the refractive index, and the thiol-containing monomer reduces the curing temperature and improves adhesion.
The formation of a high refractive index film at low temperature is achieved, the thickness, adhesion and transparency of the film are improved, and it is suitable for the light extraction layer of an organic electroluminescent device.
Smart Images

Figure 2025504513000001 
Figure 2025504513000002 
Figure 2025504513000003
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to a composition having alkali solubility. Or, one embodiment of the present invention relates to a composition for use in a cured film having a high refractive index. Or, one embodiment of the present invention relates to a cured film having a high refractive index. Or, one embodiment of the present invention relates to a method for producing a cured film having a high refractive index. Or, one embodiment of the present invention relates to a device including a cured film having a high refractive index. [Background technology]
[0002] In devices using organic materials such as organic electroluminescence elements, it is necessary to form an organic film having a high refractive index. For example, Patent Documents 1 to 4 disclose compositions containing a resin having a fluorene structure and metal oxide particles in order to form an organic film having a high refractive index.
[0003] On the other hand, the manufacture of devices using organic materials includes a process of applying and solidifying the organic material, but it is necessary to prevent the properties of the organic functional layers that constitute the device from being damaged by heating when solidifying the organic material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-196721 A [Patent Document 2] JP 2018-111777 A [Patent Document 3] JP 2019-210310 A [Patent Document 4] International Publication No. 2016 / 181422 Summary of the Invention [Problem to be solved by the invention]
[0005] One of the objects of the present invention is to provide a composition capable of forming a film at a lower temperature than conventionally. Or, in one embodiment, one of the objects is to provide a cured film having a high refractive index formed at a lower temperature than conventionally. Or, in one embodiment, one of the objects is to provide a method for producing a cured film having a high refractive index that can be formed at a lower temperature than conventionally. Or, in one embodiment, one of the objects is to provide a device including a cured film having a high refractive index formed at a lower temperature than conventionally. In addition to the above, another object is to provide a composition capable of forming a cured film having excellent haze, film thickness, and / or film adhesion, a cured film, and / or a device including the cured film. [Means for solving the problem]
[0006] According to one embodiment of the present invention, (I) a polycyclic aromatic hydrocarbon-containing polymer; (II) a scattering agent; (III) a thiol-containing monomer.
[0007] According to one embodiment of the present invention, applying the composition to a substrate to form a coating; Heating the coating film; A method for producing a cured film comprising the steps of:
[0008] According to one embodiment of the present invention, A polymer (A) derived from a polycyclic aromatic hydrocarbon-containing polymer and a thiol-containing monomer; A scattering agent; A cured film comprising the above is provided.
[0009] According to one embodiment of the present invention, there is also provided a display device comprising the cured film. Effect of the Invention
[0010] According to one embodiment of the present invention, a composition capable of forming a film at a lower temperature than conventionally is provided. Alternatively, according to one embodiment of the present invention, a cured film having a high refractive index formed at a lower temperature than conventionally is provided. Alternatively, according to one embodiment of the present invention, a method for producing a cured film having a high refractive index that can be formed at a lower temperature than conventionally is provided. Alternatively, according to one embodiment of the present invention, a device including a cured film having a high refractive index formed at a lower temperature than conventionally is provided. In addition to the above, preferably, a cured film having excellent haze, film thickness and / or film adhesion, and a device including the cured film are provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The composition, the cured film, the device including the cured film, and the method for producing the cured film according to the present invention are described below. Note that the composition, the cured film, the device including the cured film, and the method for producing the cured film according to the present invention are not to be construed as being limited to the description of the embodiments and examples shown below.
[0012] [Definition] In this specification, unless otherwise specified, the symbols, units, abbreviations and terms have the following meanings. In this specification, unless otherwise specified, the singular includes the plural, and "a" or "the" means "at least one." In this specification, unless otherwise specified, a concept element may be expressed by a plurality of kinds, and when an amount (e.g., mass % or mole %) is described, the amount means the sum of the plurality of kinds. "And / or" includes all combinations of elements and also includes the use of a single element.
[0013] In the present specification, when a numerical range is indicated using "~" or "-", it includes both endpoints and the units are the same. For example, 5 to 25 mol% means 5 mol% or more and 25 mol% or less.
[0014] In this specification, (meth)acrylate means, in accordance with common general knowledge, an acrylate, a methacrylate, or a mixture of an acrylate and a methacrylate. In this specification, a monomer refers to a monomeric unit that can form a polymer (including an oligomer) by reacting with another monomer. In this specification, the polymer may be in the form of an oligomer, and the mass average molecular weight of the polymer is not particularly limited, but is preferably 1,000 to 100,000, and more preferably 2,000 to 30,000. Here, the mass average molecular weight is the styrene-equivalent mass average molecular weight determined by gel permeation chromatography.
[0015] In this specification, the term "alkyl group" refers to a group obtained by removing one hydrogen atom from a linear or branched saturated hydrocarbon, and includes linear alkyl groups and branched alkyl groups. The term "cycloalkyl group" refers to a group obtained by removing one hydrogen atom from a saturated hydrocarbon containing a cyclic structure, and optionally includes a linear or branched alkyl group in the cyclic structure as a side chain.
[0016] In this specification, the term "aryl group" refers to a group obtained by removing one arbitrary hydrogen from an aromatic hydrocarbon. The term "alkylene group" refers to a group obtained by removing two arbitrary hydrogens from a linear or branched saturated hydrocarbon. The term "arylene group" refers to a hydrocarbon group obtained by removing two arbitrary hydrogens from an aromatic hydrocarbon.
[0017] In this specification, "C x~y ", "C x ~C y " and "C x " refers to the number of carbons in a molecule or substituent. For example, C 1~6 The alkyl group refers to an alkyl group having 1 to 6 carbon atoms (e.g., methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.). In addition, the fluoroalkyl group referred to in this specification refers to an alkyl group in which one or more hydrogen atoms have been replaced with fluorine, and the fluoroaryl group refers to an aryl group in which one or more hydrogen atoms have been replaced with fluorine.
[0018] In the present specification, when a polymer has multiple types of repeating units, these repeating units are copolymerized. The copolymerization may be any of alternating copolymerization, random copolymerization, block copolymerization, graft copolymerization, or a mixture thereof. In this specification, % means % by mass, and ratio means mass ratio.
[0019] In this specification, the unit of temperature is Celsius. For example, 20 degrees means 20 degrees Celsius. The additive refers to a compound having that function (for example, in the case of a base generator, it is a compound that generates a base). The compound may be dissolved or dispersed in a solvent and added to the composition. In one embodiment of the present invention, such a solvent is preferably contained in the composition according to the present invention as the solvent (VI) or another component.
[0020] [Composition] The composition according to one embodiment of the present invention comprises: (I) a polycyclic aromatic hydrocarbon-containing polymer; (II) a scattering agent; (III) a thiol-containing monomer; and A composition comprising at least
[0021] In one embodiment, the polycyclic aromatic hydrocarbon-containing polymer contained in the composition is preferably an alkali-soluble polymer. The composition can be used to prepare a cured film.
[0022] In one embodiment, the composition comprises: (IV) Compounds containing two or more (meth)acryloyloxy groups may include.
[0023] In one embodiment, the composition comprises: (V) Solvent It may further include:
[0024] In one embodiment, the composition comprises: (VI) Polymerization initiator It may further include:
[0025] [Polycyclic aromatic hydrocarbon-containing polymer] In this specification, the term "polycyclic aromatic hydrocarbon-containing polymer" refers to a polymer containing a repeating unit of a hydrocarbon condensed with an aromatic ring. From the viewpoint of forming a film having a high refractive index, the polycyclic aromatic hydrocarbon-containing polymer according to this embodiment is preferably a polymer having a fluorene structure (also referred to as a fluorene skeleton). More preferably, the polycyclic aromatic hydrocarbon-containing polymer according to this embodiment is a polymer having a cardo structure represented by the following chemical formula (1). [ka]
[0026] The cured film formed by the present composition containing the polymer having the above structure is suitable as a material for forming a film having a high refractive index. As mentioned above, in this specification, "polymer" is a concept that includes "oligomer". Therefore, the polycyclic aromatic hydrocarbon-containing polymer may be a polycyclic aromatic hydrocarbon-containing oligomer, and the polymer having a fluorene structure may be an oligomer having a fluorene structure. Also, the polymer having a cardo structure may be an oligomer having a cardo structure.
[0027] In one embodiment, the polycyclic aromatic hydrocarbon-containing polymer is an alkali-soluble polymer, and therefore preferably has a partial structure having an acid group. The acid group is preferably an acid group having an acid dissociation index (pKa) of 7 or less, more preferably -OH, -COOH, -SO3H, -OSO3H, -PO3H2, -CONHSO2, -SON2NHSO2-, and particularly preferably -COOH. By having such an acid group, preferably a carboxy group, the solubility of the alkali-soluble polymer in a low-concentration developer can be effectively improved.
[0028] In one embodiment, the polycyclic aromatic hydrocarbon-containing polymer may contain a repeating unit having two or more (meth)acryloyloxy groups. Also, in one embodiment, the polycyclic aromatic hydrocarbon-containing polymer contains a repeating unit having one or more acid groups. Preferably, the polycyclic aromatic hydrocarbon-containing polymer contains a repeating unit having a polycyclic aromatic hydrocarbon group, two or more (meth)acryloyloxy groups, and one or more acid groups. An example of the polycyclic aromatic hydrocarbon-containing polymer that can be contained in the present composition is a polymer containing a cardo structure represented by the following general formula (2) described in JP-A-2007-223904. [ka] (In the formula, ring Z 1 and Z 2 represent the same or different aromatic hydrocarbon rings, R 1a , R 1b , R 2a and R 2b are the same or at least one different substituent, R 3a and R 3b represent the same or different alkylene groups; k1 and k2 represent the same or different integers of 0 to 4; m1 and m2 represent integers of 0 or more; n1 and n2 represent integers of 0 or more; and q1 and q2 represent the same or different integers of 0 or more, provided that n1+n2≧2.
[0029] An example of the polycyclic aromatic hydrocarbon-containing polymer that can be contained in the present composition is a polymer containing a cardo structure represented by the following general formula (3) described in JP-A-2007-223904. [ka] (In the formula, R 1 ~R 2each independently represents a hydrogen atom, a linear, branched or cyclic alkyl or alkoxy group having 1 to 18 carbon atoms which may have a substituent, a phenyl group, a naphthyl group or a phenoxy group which may have a substituent, or a halogen atom; 1 Each independently represents a group represented by the following general formula (4) or (5). 2 each independently represents an aryl group having 6 to 24 carbon atoms or a heteroaryl group having 3 to 24 carbon atoms, which may have a substituent (excluding an amino group). [ka] (In the formula, R 3 ~R 6 each independently represents a hydrogen atom, a linear, branched or cyclic alkyl or alkoxy group having 1 to 18 carbon atoms which may have a substituent, an aryl or aryloxy group having 6 to 24 carbon atoms which may have a substituent (excluding amino group), a heteroaryl group having 3 to 24 carbon atoms, or a halogen atom. l and m represent integers of 0 to 3, and n represents an integer of 0 to 2.)
[0030] Examples of the polycyclic aromatic hydrocarbon-containing polymer that can be contained in the present composition include polymers containing a cardo structure represented by the following chemical formulas (6) to (11). [ka]
[0031] [Scattering agent] In one embodiment, the scattering agent is an organic or inorganic fine particle. Preferably, the organic fine particle is a polymer fine particle, and the inorganic fine particle is a metal oxide fine particle. More preferably, the scattering agent is an inorganic fine particle. Even more preferably, the scattering agent is an inorganic fine particle selected from the group consisting of SiO2, SnO2, CuO, CoO, Al2O3, TiO2, Fe2O3, Y2O3, ZnO, ZnS, MgO, hollow silica particles, and a mixture of one or more thereof.
[0032] In one embodiment, the scattering agent is configured to cause Mie scattering. For example, the average particle size of the scattering agent is 350 nm to 5 μm. A scattering agent having an average particle size larger than 350 nm may lead to strong forward scattering caused by Mie scattering. In addition, for good film formation, the maximum average particle size of the scattering agent is preferably 5 μm or less, more preferably 500 nm to 2 μm. From the viewpoint of ease of handling of the scattering agent and compatibility when mixed with other composition raw materials, it is preferable that the scattering agent is dispersed in an organic solvent, but it may be in a powder state. Such a scattering agent can be suitably selected from known materials, for example, products in the catalog of Ishihara Sangyo Kaisha, Ltd.
[0033] The content of the scattering agent in the composition according to the present embodiment is 50 to 400 mass% based on the total mass of the polycyclic aromatic hydrocarbon-containing polymer. The content of the scattering agent is preferably 100 to 300 mass%, more preferably 150 to 250 mass%, and more preferably 200 mass%. By including the scattering agent in these ranges, the refractive index of the cured film to be produced can be increased.
[0034] [Thiol-containing monomers] The composition according to the present embodiment contains a thiol-containing monomer, so that the temperature at which the composition solidifies can be lowered. The thiol-containing monomer is an additive that also functions as a photopolymerization initiator. The thiol-containing monomer inhibits oxygen in the atmosphere, so that the reactivity and sensitivity of the radical polymerization reaction using an unsaturated compound due to ultraviolet irradiation can be improved. As a result, the composition contains a thiol-containing monomer, so that the temperature during post-baking after ultraviolet irradiation can be lowered. In addition, the composition according to the present embodiment contains a thiol-containing monomer, so that the crosslinking property is improved and the adhesion to the underlayer is improved.
[0035] Examples of the thiol-containing monomer that can be contained in the composition according to this embodiment include the following compounds (3-1) to (3-16). [ka] [ka]
[0036] In one embodiment, the thiol-containing monomer is preferably a secondary thiol. Examples of the secondary thiol-containing monomer that can be contained in the composition according to this embodiment include the following compounds (3-17) to (3-20). [ka]
[0037] In the composition according to the present embodiment, the content of the thiol-containing monomer is 0.1 to 20 mass% based on the total mass of the polycyclic aromatic hydrocarbon-containing polymer, preferably 1 to 10 mass%, more preferably 3 to 7 mass%.
[0038] [Compounds containing two or more (meth)acryloyloxy groups] A compound containing two or more (meth)acryloyloxy groups may be referred to as a (meth)acryloyloxy group-containing compound for the sake of simplicity. Here, the (meth)acryloyloxy group is a general term for an acryloyloxy group and a methacryloyloxy group. This compound is a compound that can form a crosslinked structure by reacting with an acryloyl group-containing compound or an alkali-soluble polymer. Here, in order to form a crosslinked structure, a compound containing two or more reactive groups, acryloyloxy groups or methacryloyloxy groups, is necessary, and it is preferable to contain three or more acryloyloxy groups or methacryloyloxy groups in order to form a higher-order crosslinked structure.
[0039] As such a compound containing two or more (meth)acryloyloxy groups, an ester obtained by reacting (α) a polyol compound having two or more hydroxyl groups with (β) two or more (meth)acrylic acids is preferably used. The (α) polyol compound may be a compound having a basic skeleton of a saturated or unsaturated aliphatic hydrocarbon, an aromatic hydrocarbon, a heterocyclic hydrocarbon, a primary, secondary or tertiary amine, an ether, etc., and having two or more hydroxyl groups as a substituent. The polyol compound may contain other substituents, such as a carboxy group, a carbonyl group, an amino group, an ether bond, a thiol group, a thioether bond, etc., within the scope of not impairing the effects of the present invention.
[0040] Preferred polyol compounds include alkyl polyols, aryl polyols, polyalkanolamines, cyanuric acid, and dipentaerythritol. When the (α) polyol compound has three or more hydroxyl groups, it is not necessary that all of the hydroxyl groups are reacted with meth(acrylic acid), and they may be partially esterified. In other words, the ester may have unreacted hydroxyl groups. Examples of such esters include tris(2-acryloxyethyl)isocyanurate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol octa(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, polytetramethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, ditrimethylolpropane tetraacrylate, tricyclodecane dimethanol diacrylate, 1,9-nonanediol diacrylate, 1,6-hexanediol diacrylate, and 1,10-decanediol diacrylate. Among these, tris(2-acryloxyethyl)isocyanurate and dipentaerythritol hexaacrylate are preferred from the viewpoint of reactivity and the number of crosslinkable groups. In addition, two or more of these compounds can be combined to adjust the shape of the pattern to be formed. Specifically, it is preferable to combine a compound containing three (meth)acryloyloxy groups with a compound containing two (meth)acryloyloxy groups.
[0041] From the viewpoint of reactivity, it is preferable that such a compound has a smaller molecule than the alkali-soluble polymer, and therefore the molecular weight is preferably 2,000 or less, and more preferably 1,500 or less.
[0042] The content of the (meth)acryloyloxy group-containing compound is adjusted depending on the type of polymer or acryloyloxy group-containing compound used, and is preferably 5 to 99.9 mass%, more preferably 30 to 70 mass%, based on the total mass of the composition excluding the solvent. When combined with an alkali-soluble polymer, it is preferably 5 to 1000 mass%, more preferably 10 to 800 mass%, based on the total mass of the alkali-soluble polymer, from the viewpoint of compatibility with the alkali-soluble polymer. When a low-concentration developer is used, it is preferably 30 to 800 mass%. In addition, these (meth)acryloyloxy group-containing compounds may be used alone or in combination of two or more kinds.
[0043] [solvent] The solvent contained in the composition according to the present embodiment is not particularly limited as long as it can uniformly dissolve or disperse the above-mentioned polycyclic aromatic hydrocarbon-containing polymer, scattering agent, thiol-containing monomer, and components added as necessary. Examples of the solvent that can be used in the present invention include ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether, diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether, ethylene glycol alkyl ether acetates such as methyl cellosolve acetate and ethyl cellosolve acetate, polyethylene glycol monomethyl ether, and polyethylene glycol monoethyl ether. Examples of suitable alkoxysilanes include propylene glycol monoalkyl ethers, propylene glycol alkyl ether acetates such as PGMEA, propylene glycol monoethyl ether acetate, and propylene glycol monopropyl ether acetate, aromatic hydrocarbons such as benzene, toluene, and xylene, ketones such as methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, and cyclohexanone, alcohols such as ethanol, propanol, butanol, hexanol, cyclohexanol, ethylene glycol, and glycerin, esters such as ethyl lactate, ethyl 3-ethoxypropionate, and methyl 3-methoxypropionate, and cyclic esters such as γ-butyrolactone. Among these, from the viewpoints of availability, ease of handling, and solubility of alkali-soluble materials, it is preferable to use propylene glycol alkyl ether acetates or esters and alcohols having a straight or branched chain with an alkyl group having 4 or 5 carbon atoms.
[0044] In the composition according to the present embodiment, the content of the solvent is preferably 1000% by mass or less based on the total mass of the polycyclic aromatic hydrocarbon-containing polymer. The content of the solvent is more preferably 10 to 1000% by mass, more preferably 300 to 900% by mass, and further preferably 500 to 800% by mass. The viscosity of the composition can be adjusted by adjusting the content of the solvent contained in the composition. In one embodiment, in order to increase the thickness of the cured film formed by the composition, it is preferable to reduce the content of the solvent contained in the composition and increase the viscosity.
[0045] [Polymerization initiator] The polymerization initiator contained in the composition according to the present embodiment is a photopolymerization initiator. The photopolymerization initiator can improve the resolution by strengthening the shape of the pattern or increasing the contrast of development. The photopolymerization initiator used in the present invention is a photoradical generator that releases radicals when irradiated with light (radiation). More preferably, the polymerization initiator is configured to react to G rays (436 nm) or H rays (405 nm).
[0046] The amount of the photopolymerization initiator to be added varies depending on the type and amount of the active substance generated by the decomposition of the photopolymerization initiator, the required sensitivity, and the dissolution contrast between the exposed and unexposed parts, but is preferably 0.001 to 50 mass%, more preferably 0.01 to 30 mass%, based on the total mass of the alkali-soluble polymer. In order to prevent the dissolution contrast between the exposed and unexposed parts from being too low and not having the effect of adding, the amount added is preferably more than 0.001 mass%, and it is preferable that the amount added is less than 50 mass% in order to prevent the film formed from cracking, the coloring caused by the decomposition of the photopolymerization initiator becoming prominent, which reduces the colorless transparency of the film, the thermal decomposition of the photopolymerization initiator causing deterioration of the electrical insulation of the cured product and gas emission, which causes problems in the subsequent process, and the resistance of the film to a photoresist stripper containing monoethanolamine as a main component is reduced.
[0047] Examples of photopolymerization initiators include azo-based, peroxide-based, acylphosphine oxide-based, alkylphenone-based, oxime ester-based, and titanocene-based initiators. Among them, alkylphenone-based, acylphosphine oxide-based, and oxime ester-based initiators are preferred, and 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one are preferred. 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime).
[0048] [Cured film] The above-mentioned composition can be used to form a cured film. The cured film contains a polycyclic aromatic hydrocarbon-containing polymer, a polymer derived from a thiol-containing monomer, and a scattering agent, and the polycyclic aromatic hydrocarbon-containing polymer and the thiol-containing monomer are polymerized by a polymerization reaction. In addition, when the composition contains the above-mentioned compound containing two or more (meth)acryloyloxy groups, the aromatic hydrocarbon-containing polymer, the thiol-containing monomer, and the compound containing two or more (meth)acryloyloxy groups are polymerized to form a cured film.
[0049] The cured film has an average thickness of 1 to 20 μm. The average thickness of the cured film is preferably 1.5 to 15 μm, and more preferably 2 to 10 μm. As described above, by adjusting the viscosity of the composition according to the present embodiment, a cured film having a large thickness can be obtained.
[0050] The cured film has a refractive index of 1.6 or more at a wavelength of 550 nm. The refractive index of the cured film is preferably 1.6 to 2.3. The refractive index of the cured film is more preferably 1.7 to 2.2, and further preferably 1.8 to 2.1. A cured film having such a high refractive index is suitable as a film to be disposed on the light extraction side of an organic electroluminescent device.
[0051] The transmittance of the cured film at a wavelength of 550 nm is 60% or more. The transmittance of the cured film is preferably 60% to 99%, more preferably 70% to 98%, more preferably 80% to 95%, and even more preferably 85% to 95%. A cured film having such a high transmittance is suitable as a film to be disposed on the light extraction side of an organic electroluminescent device.
[0052] [Method of manufacturing the cured film] The method for producing a cured film includes a step of applying the composition to a substrate to form a coating film, and a step of heating the coating film. Preferably, the method for producing a cured film further includes a step of exposing the coating film to light and a step of developing the coating film. More preferably, the method for producing a cured film includes a step of applying the composition according to the present embodiment to a substrate to form a coating film, a step of exposing the coating film to light, a step of developing the coating film, and a step of heating the coating film, in this order, and further preferably includes a pre-bake step after the application step and before the exposure step. The method for forming a cured film of the present invention will be described below in the order of steps.
[0053] (1) Coating process First, the composition according to the present embodiment is applied to a substrate. The coating film of the composition according to the present embodiment can be formed by any method conventionally known as a coating method for photosensitive compositions. Specifically, the method can be selected from dip coating, roll coating, bar coating, brush coating, spray coating, doctor coating, flow coating, spin coating, slit coating, and the like.
[0054] In addition, as the substrate to which the composition is applied, a suitable substrate such as a silicon substrate, a glass substrate, or a resin film can be used. Various semiconductor elements may be formed on these substrates as necessary. When the substrate is a film, gravure coating can also be used. If desired, a drying step can be separately provided after the coating. In addition, if necessary, the coating step can be repeated once or twice or more times to form a coating film having a desired thickness.
[0055] (2) Pre-bake process After forming a coating film by applying the composition, the coating film is preferably prebaked (preheated) in order to dry the coating film and reduce the amount of solvent remaining in the coating film. The prebaking step can be carried out at a temperature of generally 40 to 150° C., preferably 50 to 100° C., for 10 to 300 seconds, preferably 30 to 120 seconds, when using a hot plate, or for 1 to 30 minutes when using a clean oven.
[0056] (3) Exposure process After the coating film is formed, the surface of the coating film is irradiated with light if desired. The light source used for the light irradiation can be any light source that has been conventionally used in pattern formation methods. Examples of such light sources include high-pressure mercury lamps, low-pressure mercury lamps, metal halide and xenon lamps, laser diodes, and LEDs. Ultraviolet rays such as g-line, h-line and i-line are usually used as the irradiating light. Except for ultrafine processing such as semiconductors, light of 360 to 430 nm (high-pressure mercury lamp) is generally used for patterning of several μm to several tens of μm. The energy of the irradiating light varies depending on the light source and the thickness of the coating film, but is generally 5 to 2000 nJ / cm.2 , preferably 10 to 1000 mJ / cm 2 In order to obtain sufficient resolution, the irradiation light energy is set to 10 mJ / cm 2 From the viewpoint of preventing exposure and the occurrence of halation, the irradiation light energy is preferably 2000 mJ / cm or more. 2 It is preferable that:
[0057] A general photomask can be used to irradiate light in a pattern. Such a photomask can be arbitrarily selected from known ones. The environment during irradiation is not particularly limited, but generally, the ambient atmosphere (air) or nitrogen atmosphere may be used. In addition, when a film is formed on the entire surface of the substrate, the entire surface of the substrate may be irradiated with light. In the present invention, the patterned film also includes the case where a film is formed on the entire surface of the substrate.
[0058] (4) Post-exposure baking process After exposure, post-exposure baking can be performed as necessary to promote the interpolymer reaction in the film by the reaction initiator generated at the exposed area. This heating process is different from the heating process (6) described later, and is not performed to completely harden the coating film, but is performed so that only the desired pattern remains on the substrate after development and the other parts can be removed by development. Therefore, it is not essential to the present invention.
[0059] When performing post-exposure heating, a hot plate, oven, furnace, or the like can be used. The heating temperature should not be excessively high because it is undesirable that the acid generated in the exposed region by light irradiation diffuses to the unexposed region. From this viewpoint, the range of the heating temperature after exposure is preferably 40°C to 150°C, more preferably 60°C to 120°C. In order to control the curing speed of the composition, stepwise heating can be applied as necessary. In addition, the atmosphere during heating is not particularly limited, but can be selected from in an inert gas such as nitrogen, under vacuum, under reduced pressure, in oxygen gas, and the like, for the purpose of controlling the curing speed of the composition. In addition, the heating time is preferably a certain amount or more in order to maintain a higher uniformity of the temperature history in the wafer surface, and is preferably not excessively long in order to suppress the diffusion of the generated acid. From this viewpoint, the heating time is preferably 20 seconds to 500 seconds, more preferably 40 seconds to 300 seconds.
[0060] (5)Developing process After exposure, if necessary, post-exposure heating is performed, and then the coating film is developed. Any developer used in the development of photosensitive compositions can be used as the developer used in the development. Preferred developers include alkaline developers that are aqueous solutions of alkaline compounds such as tetraalkylammonium hydroxide, choline, alkali metal hydroxide, alkali metal metasilicate (hydrate), alkali metal phosphate (hydrate), aqueous sodium carbonate solution, ammonia, alkylamine, alkanolamine, and heterocyclic amine, and particularly preferred alkaline developers are aqueous tetramethylammonium hydroxide solution, aqueous potassium hydroxide solution, aqueous sodium hydroxide solution, and aqueous sodium carbonate solution. These alkaline developers may further contain water-soluble organic solvents such as methanol and ethanol, or surfactants, as necessary. In the present invention, development can be performed using a developer with a lower concentration than the 2.38% by mass TMAH developer that is usually used as a developer. Examples of such a developer include a 0.05 to 1.5 mass % TMAH aqueous solution, a 0.1 to 2.5 mass % sodium carbonate aqueous solution, a 0.01 to 1.5 mass % potassium hydroxide aqueous solution, etc. The development time is usually 10 to 300 seconds, and preferably 30 to 180 seconds.
[0061] The developing method can be selected from conventionally known methods. Specific examples include immersion (dipping) in a developer, paddle, shower, slit, cap coat, spray, etc. A pattern can be obtained by this development. After development with a developer, it is preferable to wash with water.
[0062] (6)Heating process The coating film is cured by heating. The heating device used in the heating step can be the same as that used in the post-exposure heating. The heating temperature in this heating step is 70 to 120°C because the composition according to this embodiment contains a thiol-containing monomer. More preferably, the coating film is heat-cured at 75 to 100°C, and even more preferably, the coating film is heat-cured at 80 to 90°C. On the other hand, in order to promote the curing reaction and obtain a sufficient cured film, the curing temperature is preferably 70°C or higher, and more preferably 80°C or higher. The heating time is not particularly limited, and is generally 10 minutes to 24 hours, preferably 20 minutes to 3 hours. This heating time is the time after the temperature of the pattern film reaches the desired heating temperature. Usually, it takes several minutes to several hours for the pattern film to reach the desired temperature from the temperature before heating.
[0063] [Display device] The cured film according to the present embodiment can be used as a film to be disposed in a display device. Since the cured film has a high refractive index, it can be suitably applied to a display device using an organic electroluminescent element such as an organic electroluminescence display. In particular, the cured film according to the present embodiment can be suitably used as a layer to be disposed between a light-emitting layer and a surface of a display device.
[0064] Preferred embodiments are listed below.
[0065] [Embodiment 1] (I) a polycyclic aromatic hydrocarbon-containing polymer; (II) a scattering agent; (III) a thiol-containing monomer; and A composition comprising at least Preferably, the polycyclic aromatic hydrocarbon-containing polymer is an alkali-soluble polymer. In addition, the composition of the present embodiment is preferably a composition for producing a cured film.
[0066] [Embodiment 2] (I) The composition according to embodiment 1, wherein the polycyclic aromatic hydrocarbon-containing polymer comprises a fluorene structure. Preferably, it comprises a cardo structure.
[0067] [Embodiment 3] (II) The composition according to embodiment 1 or 2, wherein the scattering agent is an organic or inorganic microparticle, preferably the organic microparticle is a polymer microparticle and the inorganic microparticle is a metal oxide microparticle, more preferably the scattering agent is an inorganic microparticle, and even more preferably the scattering agent is an inorganic microparticle selected from the group consisting of SiO2, SnO2, CuO, CoO, Al2O3, TiO2, Fe2O3, Y2O3, ZnO, ZnS, MgO, hollow silica particles, and mixtures of one or more thereof. Also preferably, the scattering agent is configured to produce Mie scattering.
[0068] [Embodiment 4] The composition according to any one of embodiments 1 to 3, wherein the content of the scattering agent (II) is from 50% by mass to 400% by mass, based on the total mass of the polycyclic aromatic hydrocarbon-containing polymer (I), preferably from 100 to 300% by mass, more preferably from 150 to 250% by mass, and more preferably 200% by mass.
[0069] [Embodiment 5] The composition according to any one of embodiments 1 to 4, wherein the content of the (III) thiol-containing monomer is 0.1 to 20 mass % based on the total mass of the (I) polycyclic aromatic hydrocarbon-containing polymer, preferably 1 to 10 mass %, more preferably 3 to 7 mass %. The thiol-containing monomer is preferably a secondary thiol.
[0070] [Embodiment 6] The composition according to any one of embodiments 1 to 5, wherein (I) the polycyclic aromatic hydrocarbon-containing polymer contains a repeating unit having two or more (meth)acryloyloxy groups. Preferably, (I) the polycyclic aromatic hydrocarbon-containing polymer contains a repeating unit having one or more acid groups. Also, preferably, the polycyclic aromatic hydrocarbon-containing polymer contains a repeating unit having a polycyclic aromatic hydrocarbon group, two or more (meth)acryloyloxy groups, and one or more acid groups.
[0071] [Embodiment 7] (IV) The composition according to any one of embodiments 1 to 6, wherein the composition further comprises a compound containing two or more (meth)acryloyloxy groups. Preferably, the compound containing two or more (meth)acryloyloxy groups is a monomer.
[0072] [Embodiment 8] (V) The composition according to any one of embodiments 1 to 7, further comprising a solvent. The content of the solvent is preferably 1000% by mass or less, more preferably 10 to 1000% by mass, more preferably 300 to 900% by mass, and even more preferably 500 to 800% by mass, based on the total mass of the (I) polycyclic aromatic hydrocarbon-containing polymer.
[0073] [Embodiment 9] (VI) The composition according to any one of the first to eighth embodiments, further comprising a polymerization initiator. Preferably, the polymerization initiator is a photopolymerization initiator. More preferably, the polymerization initiator is configured to react with G rays (436 nm) and H rays (405 nm).
[0074] [Embodiment 10] A step of applying the composition according to any one of embodiments 1 to 9 to a substrate to form a coating film; A step of heating the coating film; A method for producing a cured film comprising the steps of: Preferably, the coating is heated and cured at 70 to 120°C, more preferably at 75 to 100°C, and even more preferably at 80 to 90°C.
[0075] [Embodiment 11] A cured film produced or capable of being produced by the method of embodiment 10.
[0076] [Embodiment 12] A polymer (A) derived from a polycyclic aromatic hydrocarbon-containing polymer and a thiol-containing monomer; A scattering agent; A cured film comprising:
[0077] [Embodiment 13] The cured film according to embodiment 11 or 12 has an average film thickness of 1 to 20 μm. The average film thickness is preferably 1.5 to 15 μm, and more preferably 2 to 10 μm.
[0078] [Embodiment 14] The cured film according to any one of embodiments 11 to 13, having a refractive index of 1.6 or more at a wavelength of 550 nm. The refractive index at a wavelength of 550 nm is preferably 1.6 to 2.3. More preferably, the refractive index at a wavelength of 550 nm is 1.7 to 2.2, and even more preferably, the refractive index at a wavelength of 550 nm is 1.8 to 2.1.
[0079] [Embodiment 15] The cured film according to any one of embodiments 11 to 14, having a transmittance of 60% or more at a wavelength of 550 nm. The transmittance at a wavelength of 550 nm is preferably 60 to 99%, more preferably 70 to 98%, more preferably 80 to 95%, and even more preferably 85 to 95%.
[0080] [Embodiment 16] A display device comprising the cured film according to any one of embodiments 12 to 15. Preferably, the cured film is disposed between the surface of the display device and the light-emitting layer. EXAMPLES
[0081] The present invention will be described in detail below with reference to examples. However, the present invention should not be construed as being limited to the description of the examples shown below.
[0082] [Example 1] As the polycyclic aromatic hydrocarbon-containing polymer A, an acrylic oligomer having a fluorene structure (GA-5060P, Osaka Gas Chemical Co., Ltd.) was used as 100% by mass, a scattering agent was used as 200% by mass of titania dispersion A, a thiol-containing monomer was used as 3% by mass of pentaerythritol tetrakis (3-mercaptobutyrate) (Karenz MT PE-1, Showa Denko K.K.), a compound containing two or more (meth)acryloyloxy groups was used as 20% by mass of caprolactone-modified tris-(2-acryloxyethyl) isocyanurate (A-9300-1CL, Shin-Nakamura Chemical Co., Ltd.), a photopolymerization initiator was used as 3% by mass of oxime-type elastomer (ADEKA Arcles NCI-831E, ADEKA Corporation), and a solvent was used as propylene glycol monomethyl ether acetate (Showa Denko K.K.) to prepare a solution with a solid content ratio of 35% by mass, and the composition of Example 1 was obtained.
[0083] [Example 2] Instead of scattering agent A, titania dispersion B (Ishihara Sangyo Co., Ltd.) was used as scattering agent B, and each material was added to propylene glycol monomethyl ether acetate in the ratio shown in Table 1 to prepare a solution with a solid content of 40 mass%, thereby obtaining the composition of Example 2.
[0084] [Example 3] As the polycyclic aromatic hydrocarbon-containing polymer A, an acrylic oligomer having a fluorene structure (Ogusol CR-1030, Osaka Gas Chemical Co., Ltd.) was used as 100% by mass, as the scattering agent A, 200% by mass of titania dispersion A was used as 200% by mass of the scattering agent A, as the thiol-containing monomer, 3% by mass of pentaerythritol tetrakis (3-mercaptobutyrate) (Karenz MT PE-1, Showa Denko K.K.), as the compound containing two or more (meth)acryloyloxy groups, 20% by mass of caprolactone-modified tris-(2-acryloxyethyl) isocyanurate (A-9300-1CL, Shin-Nakamura Chemical Co., Ltd.), as the photopolymerization initiator, 3% by mass of oxime-type elastomer (ADEKA Arcles NCI-831E, ADEKA Corporation), and as the solvent, propylene glycol monomethyl ether acetate (Showa Denko K.K.) was added to prepare a solution with a solid content ratio of 35% by mass, and the composition of Example 3 was obtained.
[0085] [Example 4] Instead of scattering agent A, titania dispersion B (Ishihara Sangyo Co., Ltd.) was used as scattering agent B, and each material was added to propylene glycol monomethyl ether acetate in the ratio shown in Table 1 to prepare a solution with a solid content of 40 mass%, thereby obtaining the composition of Example 4.
[0086] [Example 5] Instead of Example 1, each material was added to propylene glycol monomethyl ether acetate in the ratio shown in Table 1 to prepare a solution with a solid content ratio of 40 mass%, thereby obtaining the composition of Example 5. Titania powder (Ishihara Sangyo Kaisha, Ltd.) was used. [Comparative Example 1] The polycyclic aromatic hydrocarbon-containing polymer A was replaced with polycyclic aromatic hydrocarbon-containing polymer B, except that an acrylic monomer having a fluorene structure (Oxol GA-5060P, Osaka Gas Chemicals Co., Ltd.) was used at 100 mass%, and no scattering agent was added. Each material was added to propylene glycol monomethyl ether acetate in the ratio shown in Table 1 to prepare a solution with a solid content of 25 mass%, and the composition of Comparative Example 1 was obtained.
[0087] [Comparative Example 2] Without adding a polycyclic aromatic hydrocarbon-containing polymer, each material was added to propylene glycol monomethyl ether acetate in the ratio shown in Table 1 to prepare a solution with a solid content of 25 mass %, thereby obtaining the composition of Comparative Example 2.
[0088] [Table 1]
[0089] [Preparation of cured film] The compositions of Examples 1 to 5 and Comparative Examples 1 and 2 were applied onto a non-alkali glass substrate by spin coating (MS-A100, MIKASA), and after application, the substrate was prebaked on a hot plate (HHP-411V, AS ONE) at 100°C for 90 seconds to give an average film thickness of 2 μm. 2 After exposure, the substrate was placed in an oven (DP-200, Yamato) at 100° C. and heated for 60 minutes to promote curing of the polymer.
[0090] [Refractive index measurement] The refractive index at a wavelength of 550 nm was measured for the cured films of Examples 1 to 5 and Comparative Examples 1 and 2. An ellipsometer (M-2000, manufactured by J.A. Woollam Japan, Inc.) was used to measure the refractive index. The measurement results are shown in Table 1.
[0091] [Transmittance measurement] The transmittance at a wavelength of 550 nm was measured for the cured films of Examples 1 to 5 and Comparative Examples 1 and 2. The transmittance was measured using an ultraviolet-visible spectrophotometer (UV-2600, manufactured by Shimadzu Corporation). The measurement results are shown in Table 1.
[0092] [HAZE measurement] The haze was measured for the cured films of Examples 1 to 5 and Comparative Examples 1 and 2. In the present invention, the haze value refers to a value calculated from the ratio of diffuse transmitted light to total transmitted light, and a haze meter (NDH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure the haze. The measurement results are shown in Table 1.
[0093] [Film thickness evaluation] The film thickness of the cured films of Examples 1 to 5 and Comparative Examples 1 and 2 was evaluated. DektakXT-A (DXT-12-0489, manufactured by Bruker Japan Co., Ltd.) was used to evaluate the film thickness. The evaluation results are shown in Table 1. In Table 1, cured films with a film thickness of 5 μm or more and 10 μm or less were evaluated as A, cured films with a film thickness of 1 μm or more and less than 1 μm were evaluated as B, and cured films with a film thickness of less than 1 μm were evaluated as C.
[0094] [Adhesion evaluation] The adhesion of the cured films of Examples 1 to 5 and Comparative Examples 1 and 2 was evaluated. The adhesion was evaluated in accordance with JIS K5600-5-6. Specifically, a cross-cut method was used. The evaluation results are shown in Table 1. In Table 1, the adhesion of the cured films was evaluated as A for cured films of class 0 or 1, B for cured films of class 2 or 3, and C for cured films of class 4 or 5.
[0095] The cured films of Examples 1 to 5 exhibited a higher refractive index and a similar transmittance compared to the cured films of Comparative Examples 1 and 2. The cured films of Examples 1 to 5 had a good thickness, but the cured films of Comparative Examples 1 and 2 had an insufficient thickness. In addition, the cured films of Examples 1 to 5 and Comparative Example 1 had sufficient adhesion, but the cured films of Comparative Example 2 had insufficient adhesion.
Claims
1. (I) a polycyclic aromatic hydrocarbon-containing polymer; (II) a scattering agent; and (III) a thiol-containing monomer; and A composition comprising at least
2. The composition according to claim 1 , wherein the polycyclic aromatic hydrocarbon-containing polymer (I) contains a fluorene structure.
3. 3. The composition according to claim 1, wherein the scattering agent is an organic or inorganic fine particle.
4. The composition according to any one of claims 1 to 3, wherein the content of the scattering agent (II) is 50 to 400 mass% based on the total mass of the polycyclic aromatic hydrocarbon-containing polymer (I).
5. The composition according to any one of claims 1 to 4, wherein the content of the thiol-containing monomer (III) is 0.1 to 20 mass% based on the total mass of the polycyclic aromatic hydrocarbon-containing polymer (I).
6. The composition according to any one of claims 1 to 5, wherein (I) the polycyclic aromatic hydrocarbon-containing polymer contains a repeating unit having two or more (meth)acryloyloxy groups.
7. The composition according to any one of claims 1 to 6, further comprising (IV) a compound containing two or more (meth)acryloyloxy groups.
8. The composition according to any one of claims 1 to 7, further comprising (V) a solvent.
9. The composition according to any one of claims 1 to 8, further comprising (VI) a polymerization initiator.
10. A step of applying the composition according to any one of claims 1 to 9 to a substrate to form a coating film; Heating the coating film; A method for producing a cured film comprising the steps of:
11. A cured film produced or capable of being produced by the method of claim 10.
12. A polymer (A) derived from a polycyclic aromatic hydrocarbon-containing polymer and a thiol-containing monomer; A scattering agent; A cured film comprising:
13. The cured film according to claim 11 or 12, which has a refractive index of 1.6 or more at a wavelength of 550 nm.
14. The cured film according to any one of claims 11 to 13, having a transmittance at a wavelength of 550 nm of 60% or more.
15. A display device comprising the cured film according to any one of claims 12 to 14.
Citation Information
Patent Citations
Production method of organic-inorganic hybrid material, and epoxy resin composition
JP2015196721A
Composite resin composition and composite resin cured article
JP2018111777A
Thermally conductive composition and thermal conduction film
JP2019210310A
Transfer-type photosensitive refractive index adjustment film, method for forming refractive index adjustment pattern, and electronic component
WO2016181422A1